The Construction of an AI electronic nose system for characterization of a coffee aroma map in Chiang Rai province - Wittaya Pulsawad; Parinya Saphet; Komkrich Kaewpanus; Anusorn Tong-on; Meechai Thepnurat (Food Agricultural Sciences and Technology (FAST), 2023)
Chiang Rai, a province located in northern Thailand, has gained renown for its exclusive Arabica coffee fragrance, attributed to the region’s elevated climate and distinctive topography. In a concerted effort to elevate the worth of this aromatic treasure, a dedicated team of researchers pioneered an AI-based electronic olfaction system. The system is equipped with an array of gas sensors, meticulously calibrated to detect gases within the 10-1000 ppm range, encompassing the ten distinct gases released by coffee beans. These highly sensitive detectors are seamlessly interfaced with an Arduino ESP32 processor board and under the precise orchestration of a Python program. The system promptly responds to the sensors, meticulously gauging the nuances of the coffee aroma. Subsequently, this data is transmitted via Wi-Fi, utilizing the Internet of Things (IoT) protocol. Further, the collected information is securely deposited within a cloud-based web service, offering real-time access through an online platform. These sophisticated aroma maps serve as invaluable resources, unraveling the distinctive olfactory profiles of coffee beans cultivated across varied regions of Chiang Rai. The cumulative data serves as a cornerstone for the development of AI-driven electronic olfaction systems, tailored to identify the singular aromas of coffee beans unique to this locale. This technological leap not only enriches the repository of coffee aroma maps but also augments the inherent value of Chiang Rai’s coffee bean production. Additionally, these aroma maps serve a dual purpose by bolstering the branding and marketing endeavors of Chiang Rai’s coffee beans, rendering them easily recognizable and enticing to a global consumer audience.